PEMETAAN SPASIAL POTENSI DESA JENEMADINGING KABUPATEN GOWA SULAWESI SELATAN - Abdul Malik; Abd Rahim; Rahmat Hidayat; Nurhamdi Nurhamdi; Andi Fatimah; Rini Anggraini; Adela Pradinianti Haris; Adelin Adelin; Andi Nursakina (UNIVERSITAS NEGERI MAKASSAR, 2022)
The presence of spatial-based data and information represented in thematic maps of the potential resources owned by villages is an essential requirement in supporting village development. This study aims to map the potential of Jenemandinging Village based on geospatial information by providing a village database that includes population, area and boundaries, land use, and infrastructure and facilities. Data collection in this study included secondary data collection, Focus Discussion Group (FGD), and surveys and mapping of infrastructure and facilities owned by the village. Survey and mapping were conducted by plotting coordinates (coordinate marking points) using handheld GPS and aerial drone recording and taking photos as documentation. The GCP/ICP control point data were then analyzed using Real-Time Kinematic (RTK) and Static methods to produce tested orthophotos and digitized to produce thematic maps. The results of this study promise an information map and spatial data, which includes village administrative thematic maps containing information on village area and boundaries, land use, and infrastructure and facilities (road network, drainage, electricity, public facilities, educational facilities, and worship facilities). Besides that, population attribute data is also produced. This spatial data and information can be a primary reference in making decisions in the village development framework, including promoting the village's potential.